Effects of cognitive behaviour therapy for worry on persecutory delusions in patients with psychosis (WIT): a parallel, single-blind, randomised controlled trial with a mediation analysis. (April 2015) - Freeman, Daniel; Dunn, Graham; Startup, Helen; Pugh, Katherine; Cordwell, Jacinta; Mander, Helen; Černis, Emma; Wingham, Gail; Shirvell, Katherine; Kingdon, David
Summary Background Worry might be a contributory causal factor in the occurrence of persecutory delusions in patients with psychotic disorders. Therefore we postulated that reducing worry with cognitive behaviour therapy (CBT) would reduce persecutory delusions. Methods For our two-arm, assessor-blinded, randomised controlled trial (Worry Intervention Trial [WIT]), we recruited patients aged 18–65 years with persistent persecutory delusions but non-affective psychosis from two centres: the Oxford Health National Health Service (NHS) Foundation Trust (Oxford, UK) and the Southern Health NHS Foundation Trust (Southampton, UK). The key inclusion criteria for participants were a score of at least 3 on the Psychotic Symptoms Rating Scale (PSYRATS) denoting a current persecutory delusion; that the delusion had persisted for at least 3 months; a clinical diagnosis of schizophrenia, schizoaffective disorder, or delusional disorder; and a clinically significant level of worry. We randomly assigned (1:1) eligible patients, using a randomly permuted block procedure with variable block sizes and division by four strata, to either six sessions of worry-reduction CBT intervention done over 8 weeks added to standard care (the CBT-intervention group), or to standard care alone (the control group). The assessors were masked to patient allocations and did their assessments at week 0 (baseline), 8 weeks (end of treatment), and 24 weeks, follow-up. The primary outcomes were worry measured by the Penn State Worry Questionnaire (PSWQ) and delusions measured by the PSYRATS-delusion scale; we did the analyses in the intention-to-treat population, and also did a planned mediation analysis. This trial is registered with the ISRCTN Registry (number ISRCTN23197625) and is closed to new participants. Findings From Nov 1, 2011, to Sept 9, 2013, we recruited 150 eligible participants and randomly assigned 73 to the CBT intervention group, and 77 to the control group. 143 patients (95%) provided primary outcome follow-up data. Compared with standard care alone, at 8 weeks the CBT intervention significantly reduced worry (mean difference 6·35 [SE 1·56] PSWQ units, 95% CI 3·30–9·40; p<0·001) and persecutory delusions (2·08 [SE 0·73] PSYRATS units, 95% CI 0·64–3·51; p=0·005). The reductions were maintained to 24 weeks follow-up. The mediation analysis suggested that the change in worry accounted for 66% of the change in delusion. No patients died or were admitted to secure units during our study. Six suicide attempts (two in the CBT intervention group, and four in the control group) and two serious violent incidents (one in each group) were noted, but no adverse events were deemed related to the treatments or the assessments. Interpretation To our knowledge, this is the first large trial focused on persecutory delusions. We have shown that long-standing delusions were significantly reduced by a brief intervention targeted on worry, although the limitations for our study include no determination of the key elements within the intervention. Our results suggest that worry might cause paranoia, and that worry intervention techniques might be a beneficial addition to the standard treatment of psychosis. Funding Efficacy and Mechanism Evaluation programme, which is a UK Medical Research Council and National Institute of Health Research partnership.